Comparative Pharmacokinetics/Pharmacodynamics of Fixed-Dose Combination of Esomeprazole and Calcium Carbonate (AD-206) to the Conventional Esomeprazole - Bae S; Kwon J; Lee SB; Jang IJ; Yu KS; Lee S (Dove Medical Press, 2021)
Sungyeun Bae,1 Jihoon Kwon,2 Si-Beum Lee,3 In-Jin Jang,1 Kyung-Sang Yu,1 SeungHwan Lee1 1Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Republic of Korea; 2Statistics Team, APACE, Seoul, Republic of Korea; 3Addpharma Pharmaceutical Corp, Seongnam-si, Gyeonggi, Republic of KoreaCorrespondence: SeungHwan LeeDepartment of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, 101 Daehak-ro, Jongno-gu, Seoul, 03080, Republic of KoreaTel +82-2-2072-1920Fax +82-2-742-9252Email leejh413@snu.ac.krPurpose: Proton pump inhibitors (PPIs) are used for the treatment of acid-related disorders. Demands for enhanced stability and faster onset led to the development of AD-206, a fixed-dose combination of a PPI (esomeprazole) with an antacid salt (calcium carbonate). This study compared the pharmacokinetics (PKs) and pharmacodynamics (PDs) of AD-206 (Addpharma) with conventional esomeprazole (Nexium®, AstraZeneca).Materials and Methods: A randomized, open-label, two-treatment, two-sequence crossover study was conducted with 2 different doses of esomeprazole at 20 and 40 mg with a fixed calcium carbonate dose of 600 mg in AD-206. Forty-four subjects were included in each dose group and randomly received either AD-206 or the conventional esomeprazole for 7 consecutive days in each period. After a single- and multiple-dose, blood samples for the PK analysis were analyzed, and 24-hour intragastric pH monitoring was conducted.Results: The systemic exposure of esomeprazole after a multiple-dose of AD-206 was similar to that of the conventional esomeprazole in both doses, but the time to reach the peak concentration was faster in AD-206. The percentage decrease from baseline in the integrated gastric acidity for a 24-hour interval after the dose was not significantly different between the AD-206 and the conventional esomeprazole after a single- and multiple-dose for both doses, and the time to reach pH 4 was faster for AD-206.Conclusion: AD-206 showed a similar systemic exposure and suppression of gastric acid secretion after a multiple-dose compared to the conventional esomeprazole.Keywords: proton pump inhibitors, randomized controlled study, crossover design, healthy subjects, intragastric pH monitoring